2001
DOI: 10.1074/jbc.m106438200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Ligand Binding Properties of Neuroglobin, a Novel Member of the Globin Family

Abstract: Neuroglobin is a recently discovered member of the globin superfamily that is suggested to enhance the O 2 supply of the vertebrate brain. Spectral measurements with human and mouse recombinant neuroglobin provide evidence for a hexacoordinated deoxy ferrous (Fe 2؉ ) form, indicating a His-Fe 2؉ -His binding scheme. O 2 or CO can displace the endogenous protein ligand, which is identified as the distal histidine by mutagenesis. The ferric (Fe 3؉ ) form of neuroglobin is also hexacoordinated with the protein li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
625
3
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 428 publications
(678 citation statements)
references
References 36 publications
(44 reference statements)
36
625
3
5
Order By: Relevance
“…In neuroglobin, mutation of His to Leu in the E helix increases the ligand-binding constants, indicating that the endogenous ligand can be replaced by external ligands such as oxygen and carbonic monoxide. 46 Based on their spectroscopic analysis, Sawai et al 47 also suggested that His residue is responsible for the globin conformer structure and heme-ligand binding. These findings support experiments demonstrating that the heme domain is an important contributor to radical scavenging.…”
Section: Discussionmentioning
confidence: 99%
“…In neuroglobin, mutation of His to Leu in the E helix increases the ligand-binding constants, indicating that the endogenous ligand can be replaced by external ligands such as oxygen and carbonic monoxide. 46 Based on their spectroscopic analysis, Sawai et al 47 also suggested that His residue is responsible for the globin conformer structure and heme-ligand binding. These findings support experiments demonstrating that the heme domain is an important contributor to radical scavenging.…”
Section: Discussionmentioning
confidence: 99%
“…The CH-IQ-AB domain was PCR-amplified for further cloning from the pENTR4 ADGB vector. The NGB domain was PCR-amplified from pET3a NGB construct, which was already available in our laboratory [15]. For the cloning of CH-IQ-AB in the pPicZα vector, the cDNA of the fragment was synthesized by Invitrogen GeneArt, with optimized codons for expression in P.pastoris.…”
Section: Construction Of the Recombinant Expression Vectorsmentioning
confidence: 99%
“…The estimated amount of Ngb in the vertebrate brain under non-pathological conditions is only in the micromolar range. It was possible to perform a biochemical and structural characterization of NGB subsequent to the recombinant expression of the protein in E.coli [15].…”
Section: Introductionmentioning
confidence: 99%
“…While hxHbs can bind oxygen and other exogenous ligands, kinetic and equilibrium analysis of the reactions is much more complex than the bimolecular reactions observed with pentacoordinate Hbs due to competition from intramolecular coordination of the binding site. While many functions have been proposed for hxHbs from different organisms, and they have the biochemical capabilities to perform many reactions (4), no clear role has yet been supported to the exclusion of others (6,(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Flash photolysis and rapid mixing have been used to examine ligand binding kinetics in many hxHbs, and both techniques have revealed multiphasic time courses for oxygen and carbon monoxide binding that cannot be accounted for using simple reaction models. In an effort to extract useful binding constants, it has been necessary to disregard heterogeneity in reaction time courses (6,11,12,16,17). For this reason, different binding constants have been reported for some hxHbs that are dependent on how the reactions are initiated or on what time scales they are analyzed (16,17).…”
mentioning
confidence: 99%